The Leader's Intellect in the Malay Expressions of Tenas Effendy found in Sulalat u's Salatin (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
According to Tenas Effendy (2000), as a "wise" person, a leader ought to be knowledgeable, possess wisdom and intellect, and be close to the people he leads. He further explained that a leader is required to possess a good soul and admirable personality. It is necessary for a leader to possess worldly knowledge and religious knowledge so he can lead and be guided appropriately and adequately. With such knowledge, the leader will know how to evaluate and adjudicate disputes, or problems that may arise, wisely. A visionary leader is also emphasized by Tenas Effendy in his ungkapan, or expressions. Through his ungkapan, this study aims to examine aspects of the intellect that exist in the acclaimed Sulalat u's Salatin, or Malay Annals. Several events will be cited as the basis for this study's discussion. There are 29 important events that were extracted from the text. For every concept of intellect that was extracted, there are several sub-categories belonging to it. As a Malay of refined character, every ungkapan written by Tenas Effendy is an apt advice. As such, the exquisite arrangement of the stanzas and meticulous writing about the position of the leader can be experienced in his ungkapan. In conclusion, this study examines the position of the intellect as the main principle that must be possessed in a leader when ruling an empire, especially one that is vulnerable to various other parties.